2022
DOI: 10.1111/dmcn.15193
|View full text |Cite
|
Sign up to set email alerts
|

A novel risk calculator predicting surgical site infection after spinal surgery in patients with cerebral palsy

Abstract: Surgical site infection (SSI) after pediatric spine surgery is a well-recognized complication. Since the year 2000, the reported risk of SSI in pediatric spine surgery ranges from 0% to 26.3% in the USA. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Most of these studies have found that patients with non-idiopathic deformities, including cerebral palsy (CP), are at increased risk of SSI compared with those with idiopathic etiologies. 1,3,4,16 Treatment of SSI entails surgical irrigation and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 54 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…In a study of pediatric CP patients undergoing spinal fusion, a final SSI risk prediction model included behavioral disorder/delay as a risk factor. 18 Conclusions: There is grade B evidence that baseline cognitive/behavioral impairments are associated with an increased risk of SSI after NMS surgery in pediatric populations, although this is likely confounded by underlying etiology.…”
Section: Cognitive/behavioral Statusmentioning
confidence: 99%
See 4 more Smart Citations
“…In a study of pediatric CP patients undergoing spinal fusion, a final SSI risk prediction model included behavioral disorder/delay as a risk factor. 18 Conclusions: There is grade B evidence that baseline cognitive/behavioral impairments are associated with an increased risk of SSI after NMS surgery in pediatric populations, although this is likely confounded by underlying etiology.…”
Section: Cognitive/behavioral Statusmentioning
confidence: 99%
“…Two Level III studies identified baseline urinary/ bowel incontinence as a risk factor for postoperative SSI among CP-scoliosis or any NMS patients, with odds ratios of 2.5 and 2.4, respectively. 18,50 Conclusions: There is grade B evidence that urinary/ bowel incontinence is associated with greater risk of SSI after NMS surgery in pediatric populations.…”
Section: Bladder/bowel Incontinencementioning
confidence: 99%
See 3 more Smart Citations